من الأنثروبولوجيا عموما إلى أنثروبولوجيا البلاد المغاربيّة - معروف, نذير (Changement Social; No 03 (2017): مجــــلة التغير الاجتماعي, 2018)
تمثل الأنثروبولوجيا اختصاصا ظلت حدوده على الدوام مُلْتَبِسَة ولم تتوقّف توجهاتُه عن التغيّر بمراعاة السياق، وذوق العصر والإيديولوجيات. مرّ تاريخها بالمراحل التالية: 1)الرومنسية. 2)الكانتية المستندة على الموروث الأرسطي. 3)الدوركايمية. الاستعمارية . 4)ما بعد الكولونيالية. سيطرت عليها ثلاثة توجهات أساسية أنتجتها ثلاث مدارس؛ الفرنسية والإنجليزية والأمريكية. بالنسبة للجزائر في هذه المرحلة الأخيرة؛ تقاطعت شبكات التحليل من بنيوية ووظيفية وانتشارية، وكان هناك سياق تسبب في تهجير البحث من البلاد المُستعمَرة سابقا إلى البلاد المستعمِرة، كما توجه البحث إلى معالجة الظاهرة الفولكلورية بغرض تثمين التراث،. واتُّخِذَ موقف رسمي يرى بأنه ليس هناك مكان إلاّ لعلوم اجتماعية تسهم في البناء الوطني والتنمية واعتُبِرت الأنثروبولوجيا علما استعماريا. كما أصبحت المعطيات الجديدة للدولة الوطنية وللبورجوازيات الناشئة ولاقتصاديات الدول النامية  والخدمات موضوعات مميزة للدراسة الأنثروبولوجية. Anthropologyis a specialtywhosebounderies have always been ambiguous and whose directions has not ceased to change by takingintoconsideration : the context, the taste of the times and ideologies. It has a history of the following stages: 1/Romantic 2/Cantonesebased on the heritage of Aristotle 3/Durkheimia 3/Colonial 4/Postcolonialism. It wasdominated by 3 main orientations produced by 3 schools : French, English and American. As for Algeria in this last stage, the networks of analysiscrossedfrom structural, functional and pervasive, and therewas a contextthatcaused the displacement of the researchfrom the former colonial country to the colonised country. The researchalsosought to address the folklore phenomenon for the purpose of valuing the heritage and took the official position thatthereis no place except for social sciences whichcontribute to national construction and development and consideredanthropology to becolonial . The new data of the national state, the emerging bourgeoisie, the economies of developing countries and  services have become distinctive subjects of the study of anthropology.